Virion structures and genome delivery of honeybee viruses - Procházková, Michaela; Škubník, Karel; Füzik, Tibor; Mukhamedova, Liya; Přidal, Antonín; Plevka, Pavel (Current opinion in virology, 2020)
The western honeybee is the primary pollinator of numerous food crops. Furthermore, honeybees are essential for ecosystem stability by sustaining the diversity and abundance of wild flowering plants. However, the worldwide population of honeybees is under pressure from environmental stress and pathogens. Viruses from the families Iflaviridae and Dicistroviridae, together with their vector, the parasitic mite Varroa destructor, are the major threat to the world's honeybees. Dicistroviruses and iflaviruses have capsids with icosahedral symmetries. Acidic pH triggers the genome release of both dicistroviruses and iflaviruses. The capsids of iflaviruses expand, whereas those of dicistroviruses remain compact until the genome release. Furthermore, dicistroviruses use inner capsid proteins, whereas iflaviruses employ protruding domains or minor capsid proteins from the virion surface to penetrate membranes and deliver their genomes into the cell cytoplasm. The structural characterization of the infection process opens up possibilities for the development of antiviral compounds.
Keywords: virové nemoci; Animals; virion; Genome, Viral; Hydrogen-Ion Concentration; Capsid; kapsida; genom virový; Virion; Capsid Proteins; krystalografie rentgenová; Virus Diseases; Models, Molecular; kyseliny; Protein Conformation; molekulární modely; RNA Viruses; virové plášťové proteiny; Bees; konformace proteinů; RNA-viry; včely; zvířata; Crystallography, X-Ray; koncentrace vodíkových iontů; Acids